1951
DOI: 10.1111/j.1365-2044.1951.tb01885.x
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Hypotension by Arteriotomy in Tntracranial Surgery

Abstract: FROM 7 H t IIbPT. OE SURGICAL NEUROLOGY, ROYAL INFIRMARY, EVINBURGH.THE problem of bleeding during operations has long exercised the minds of surgeons. This problem has two aspects: first, the danger to life from loss of blood, and second, the inconvenience to the surgeon of a blood-obscured operation field. With the ready availability of stored blood, the first part of t4e problem is no longer so formidable. The second, that of bleeding in the field of operation, still awaits a satisfactory solution. In surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
1

Year Published

1953
1953
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Later, Gardner (1946) described a method of controlled induced hypotension by arteriotomy. Further trials of the same technique have been reported by Bilsland (1951) and Mortimer (1951). In this method the factor responsible for preventing excessive bleeding is the compensatory vasoconstriction which follows the reduction of blood-volume.…”
mentioning
confidence: 80%
“…Later, Gardner (1946) described a method of controlled induced hypotension by arteriotomy. Further trials of the same technique have been reported by Bilsland (1951) and Mortimer (1951). In this method the factor responsible for preventing excessive bleeding is the compensatory vasoconstriction which follows the reduction of blood-volume.…”
mentioning
confidence: 80%
“…In addition to trials with arteriotomy (Bilsland 1951), high spinal anaesthesia has been employed concomitantly to facilitate surgery (Sarnoff & Arrowood 1946, Lynn et al 1952. Thus surgery on the hip which was considered a serious undertaking has been rendered more beneficial and without grave after effects (Kern 1952, Welch et al 1975, Donaldson 1975.…”
Section: Discussionmentioning
confidence: 99%
“…The earlier hypotensive techniques of arteriotomy (Bilsland 1951) were abandoned in favour of more beneficial methods when the autonomic ganglion blocking agents were introduced, providing a relatively avascular field for surgical procedures (Royester et al 1951, Steven & Tovell 1954, Holms 1956, Nayman 1960. Deliberate hypotension has been employed in thoracic surgery (Lewis 1951), prostatic surgery (Bruce 1960) and in large blood vessel surgery (Glenn e t al.…”
mentioning
confidence: 99%
“…70 Proposed benefits include 1) reduced intraoperative blood loss, 2) improved surgical visualization, 3) shortened operative time, and 4) decreased use of and exposure to blood products. 43 The efficacy and safety of this technique have been studied in general plastic surgery, 18,19,23,36,43,72 neurosurgery, 1,3,24,25,28,31,47,48,57,62,74 maxillofacial surgery, 4,7,16,20,21,38,51,54,59,60,73 orthopedic surgery, 2,6,17,35,41,44,46,52,53,67,69 general surgery, 15,33,65 otolaryngology, 8,29,55,56,61,71 bur...…”
mentioning
confidence: 99%